2020
DOI: 10.33988/auvfd.695432
|View full text |Cite
|
Sign up to set email alerts
|

The role of micronutrients in high-yielding dairy ruminants: Choline and vitamin E

Abstract: This review addresses the potential role of antioxidants and methyl-group sources in optimising the metabolic health of dairy ruminants. The productivity of high-yielding dairy cows has increased over the past 40 years and the milk yield has doubled. Such increases in milk production have been observed not only in dairy cows but also to some extent in other dairy ruminants such as ewes, goats and buffaloes (Bubalus bubalis). As a consequence, in all specialized dairy ruminants it is essential to optimize the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
13
0
3
Order By: Relevance
“…Other studies confirmed the importance of choline supplementation in increasing not only milk production (yield and composition) but also choline-containing compounds in milk derived from dairy ruminants [12,[50][51][52][53][54][55].…”
Section: Lipids In Mfg and Mfgm And The Role Of Cholinementioning
confidence: 91%
“…Other studies confirmed the importance of choline supplementation in increasing not only milk production (yield and composition) but also choline-containing compounds in milk derived from dairy ruminants [12,[50][51][52][53][54][55].…”
Section: Lipids In Mfg and Mfgm And The Role Of Cholinementioning
confidence: 91%
“…To our knowledge, numerous detailed reviews about the disease risk of hypovitaminosis E and the α-Toc supplementation effect on the health of transition dairy cows and heifers have been published in the last 30 years (two databases, PubMed and Web of Science were searched using key words: vitamin E, dairy cows, tocopherol, 1990–2021, and reviewed full text is currently available online, 1990s: [ 17 , 18 , 19 , 20 , 21 , 22 ], 2000s: [ 1 , 23 , 24 , 25 , 26 , 27 ], 2010s: [ 28 , 29 , 30 , 31 , 32 ]). Based on three recent reviews published in the last 10 years [ 30 , 31 , 32 ], α-Toc supplementation has the potential to affect the incidence of mastitis, including milk somatic cell count (SCC) values, and retained foetal membranes (RFM). Some studies suggest that α-Toc supplementation at the level 1000 to 4000 IU/day/cow during the dry period can reduce the frequency of intramammary infection and the occurrence of clinical mastitis, as well as the levels of SCC in milk [ 17 , 133 , 141 ], suggesting that α-Toc deficiency may be a critical risk factor for the increased frequency of infection and duration in mammary glands during the transition period.…”
Section: Hypovitaminosis E In Transition High-yield Dairy Cowsmentioning
confidence: 99%
“…To our knowledge, numerous detailed reviews about the disease risk of hypovitaminosis E and the α-Toc supplementation effect on the health of transition dairy cows and heifers have been published in the last 30 years (two databases, PubMed and Web of Science were searched using key words: vitamin E, dairy cows, tocopherol, 1990-2021, and reviewed full text is currently available online, 1990s: [17][18][19][20][21][22], 2000s: [1,[23][24][25][26][27], 2010s: [28][29][30][31][32]). Based on three recent reviews published in the last 10 years [30][31][32], α-Toc supplementation has the potential to affect the incidence of mastitis, including milk somatic cell count (SCC) values, and retained foetal membranes (RFM).…”
Section: Disease Risk In Hypovitaminosis E and The Effects Of α-Toc Supplemantetion In Transition Dairy Cowsmentioning
confidence: 99%
See 1 more Smart Citation
“…When plasma level of α-tocopherol was more than 3 µg/mL during calving, the clinical mastitis did not occur in cows (Weiss et al, 1997). Panda and Kaur (2005) and Pinotti et al (2020) indicated that the decreasing of α-tocopherol and total antioxidant activity at parturition could be minimized by prepartum supplementation of vitamin E.…”
Section: Vitamin a And E Status During Periparturient Periodmentioning
confidence: 99%